2013
DOI: 10.5402/2013/425831
|View full text |Cite
|
Sign up to set email alerts
|

Virus and Antibody Diagnostics for Swine Samples of the Dominican Republic Collected in Regions Near the Border to Haiti

Abstract: The Dominican Republic (DR) and Haiti share the island of Hispaniola, and reportable transboundary animal diseases have been introduced between the two countries historically. Outbreaks of severe teschovirus encephalomyelitis in pigs began occurring in Haiti in February 2009, and a field and laboratort study in April 2010 indicated that the teschovirus disease is prevalent in many regions in Haiti including areas near the border with DR and that other viral disease agents, including CSF virus (CSFV), porcine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…To date, outbreaks of mild disease have been described in the United States [ 4 , 5 , 6 , 7 ], although the most severe form of TE caused by highly virulent strains of PTV-1 has not been reported. However, outbreaks of TE due to PTV-1 have been recently reported in Haiti, Dominican Republic, and Canada [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, outbreaks of mild disease have been described in the United States [ 4 , 5 , 6 , 7 ], although the most severe form of TE caused by highly virulent strains of PTV-1 has not been reported. However, outbreaks of TE due to PTV-1 have been recently reported in Haiti, Dominican Republic, and Canada [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Porcine enteric picornaviruses have been reported in domestic pigs and wild boars in Asia [3][4][5][6], Europe [7][8][9][10], North America [11,12], Central America [13,14], and South America [15,16]. Pigs of all ages are susceptible to infection with TV-A, SV-A, and EV-G, which are viruses that circulate worldwide in asymptomatic domestic pigs [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, depending on the virus serotype and infection conditions, these picornaviruses may be considered important etiological agents of enteric, respiratory, reproductive, or neurological disorders (Bangari et al 2010, Ventura et al 2013. Clinical manifestations may include diarrhea, pneumonia, febrile illness, vesicular diseases, reproductive failure (SMEDI syndrome), myocarditis, and polioencephalomyelitis (Krumbholz et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed in different geographical regions throughout the world revealed that PTV, PSV, and EV-G are ubiquitous and have been reported in Asia (Kaku et al 2007, Lan et al 2011, Lin et al 2012, Moon et al 2012, Zhang et al 2012, Europe (Zell et al 2000, La Rosa et al 2006, Buitrago et al 2010, Sozzi et al 2010, Boros et al 2011, Prodělalová 2012, and the Americas (Bangari et al 2010, Salles et al 2011, Shan et al 2011, Deng et al 2012, Ventura et al 2013, Donin et al 2014.…”
Section: Introductionmentioning
confidence: 99%